Antidiabetic and Antioxidant Activity of Ethanolic Extract of Sapindus Trifoliatus Linn. - P.K Sahoo; K.M Padhy,D. Pradhan; G. Tripathy; R Bhoi; S.Pattanayak; S K Sahoo (International Journal of Pharma and Bio Sciences, 2010)
The treatment of diabetes mellitus has been confined to use of oral hypoglycemic agents and insulin, due to having serious side effects. This leads to increasing demand for herbal products with antidiabetic factor with less side effects. This manuscript describes the antihyperglycaemic activity, in vivo antioxidant potential, effect on glycosylation of hemoglobin and in-vitro peripheral utilisation of glucose of the ethanolic extract of the aerial parts of Sapindus trifoliatus. The extract produced significant decrease in the blood glucose level when compared with the controls in alloxan induced hyperglycemic rats both in the single dose as well as multiple dose experiment at the tested dose level and is comparable with the standard drug glibenclamide. It was observed that the ethanolic extract reversed the weight loss of the diabetic rats and they returned to near normal. The extract prevented significant elevation of glycosylated hemoglobin in vitro, with IC50 value being 12.5 µg/ml that is comparable with the reference drug α-tocopherol. Administration of the extract and glibenclamide significantly decreased the levels of TBARS, increased the content of GSH and increased the activity of SOD and CAT in liver of diabetic rats. The extract increased peripheral glucose utilisation in the diaphragm of diabetic rats in vitro, which is comparable with the action of insulin. Thus, the extract might have insulin like activity and the antihyperglycemic effect of the extract might be due to an increase in peripheral glucose consumption as well as protection against oxidative damage in alloxan induced diabetes.